Arrhythmogenic Mechanisms in Hypokalaemia: Insights From Pre-clinical Models - Tse, Gary; Li, Ka Hou Christien; Cheung, Chloe Kwong Yee; Letsas, Konstantinos P.; Bhardwaj, Aishwarya; Sawant, Abhishek C.; Liu, Tong; Yan, Gan-Xin; Zhang, Henggui; Jeevaratnam, Kamalan; Sayed, Nazish; Cheng, Shuk Han; et al. (Frontiers in Cardiovascular Medicine, 2021)
Potassium is the predominant intracellular cation, with its extracellular concentrations maintained between 3.5 and 5 mM. Among the different potassium disorders, hypokalaemia is a common clinical condition that increases the risk of life-threatening ventricular arrhythmias. This review aims to consolidate pre-clinical findings on the electrophysiological mechanisms underlying hypokalaemia-induced arrhythmogenicity. Both triggers and substrates are required for the induction and maintenance of ventricular arrhythmias. Triggered activity can arise from either early afterdepolarizations (EADs) or delayed afterdepolarizations (DADs). Action potential duration (APD) prolongation can predispose to EADs, whereas intracellular Ca2+ overload can cause both EADs and DADs. Substrates on the other hand can either be static or dynamic. Static substrates include action potential triangulation, non-uniform APD prolongation, abnormal transmural repolarization gradients, reduced conduction velocity (CV), shortened effective refractory period (ERP), reduced excitation wavelength (CV x ERP) and increased critical intervals for re-excitation (APD – ERP). In contrast, dynamic substrates comprise increased amplitude of APD alternans, steeper APD restitution gradients, transient reversal of transmural repolarization gradients and impaired depolarization-repolarization coupling. The following review article will summarize the molecular mechanisms that generate these electrophysiological abnormalities and subsequent arrhythmogenesis.